The Effectiveness of the Revitalization of “Jogo Tonggo” as Local Wisdom in Vigilance and Prevention of Transmission of COVID-19 in Central Java Province - Yulianto Prabowo; Agus Suwandono; Bagoes Widjanarko; Sutopo Patriajati; Aris Sugiharto (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Jogo tonggo is an empowerment effort to increase community participation in preventing thetransmission and spread of Covid-19 in Central Java. The study aims to assess the effectiveness of the revitalizationof “jogo tonggo” as local wisdom toward increasing community knowledge, attitudes, and behavior towardCOVID-19.Methods: This study is true-experimental study involving 352 respondents, which are divided into the experimentalgroup and the control group. The used statistical analyses were paired simple t-test, independent t-test, Mann-Whitney, and Wilcoxon.Results: There was an increase in the mean after intervention between group 1 and group 2 including knowledgeof “jogo tonggo” (δ=2.39; p=0.001), knowledge of COVID-19 symptoms and transmission modes (δ=2.87; p=0.001),knowledge of prevention methods of COVID-19 (δ=1.63; p=0.001), attitudes towards “jogo tonggo” (δ=2.00;p=0.004), attitudes towards COVID-19 (δ=1.58; p=0.011), and COVID-19 prevention behavior (δ=6.04; p=0.001).Conclusion: The revitalization of “jogo tonggo” can increase knowledge, attitudes, and behavior toward COVID-19.